Influence of tobacco, alcohol consumption, eating habits and physical activity in nursing students - Pedro Manuel Rodríguez-Muñoz; Juan Manuel Carmona-Torres; María Aurora Rodríguez-Borrego (Universidade de São Paulo, 2020)
Objective: to determine the consumption of alcohol, tobacco, eating habits, and physical activity among nursing students and to detect whether being a nursing student is a protective factor against these habits. Method: a questionnaire was used to collect information on age, academic year, sex, alcohol and tobacco consumption, physical activity, and healthy eating. An information sheet and informed consent form were given. The sample was composed of 264 students aged between 18-30 years from four academic years. Results: of the total sample, 15.5% smoked, 83.7% consumed alcoholic beverages and 97.2% consumed over the weekend. The total of 68.6% did not practice exercises and 70.5% needed changes in their diet. Conclusion: nursing students have high levels of alcohol consumption and low levels of smoking compared with other studies. The higher the academic year, the lower the age of onset of tobacco consumption. The number of men who exercised was higher, which is considered a protective factor against alcohol and tobacco consumption and is related to a healthy diet. Smoking has a negative influence on diet. The students needed to change their diet. Finally, being a nursing student is not considered a protective factor against alcohol and tobacco consumption, nor having good eating habits and exercising.